2011
DOI: 10.2478/s13382-011-0032-0
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis B and C viruses: Awareness and safe practices of hairdressers in Izmir — A survey

Abstract: Objectives: The aim of the study is to determine the seroprevalence of hepatitis B (HBV) and hepatitis C virus (HCV) infection in barbers and to assess the awareness of these employees related to occupational risks of HBV and HCV. Materials and Methods: In this study, 2145 barbers in Izmir were given an occupational safety seminar. Blood samples were collected from 2066 voluntary participants and 1284 individuals completed the questionnaires. Sera were tested for the presence of HBV and HCV markers by ELISA. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 17 publications
(21 reference statements)
1
13
3
Order By: Relevance
“…This HCV prevalence was different from other studies among beauticians in Ghana (0.5%), 30 Brazil (0.8%), 10 Izmir, Turkey (0.9%), 29 Morocco (1.7%), 28 Teheran, Iran (2.0%), 25 Sivas, Turkey (2.8%), 37 and Pakistan (6.97%). 38 We may not have had a sufficient sample size to detect HCV infection in a low prevalence population, and we calculated our sample size based on estimating HBV prevalence, not HCV prevalence.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…This HCV prevalence was different from other studies among beauticians in Ghana (0.5%), 30 Brazil (0.8%), 10 Izmir, Turkey (0.9%), 29 Morocco (1.7%), 28 Teheran, Iran (2.0%), 25 Sivas, Turkey (2.8%), 37 and Pakistan (6.97%). 38 We may not have had a sufficient sample size to detect HCV infection in a low prevalence population, and we calculated our sample size based on estimating HBV prevalence, not HCV prevalence.…”
Section: Discussioncontrasting
confidence: 47%
“…Comparing HBV prevalence among beauticians in our study with studies among beauticians in other countries, our study population had a higher HBV prevalence than that from studies in Iran (1.1%), 25 Morocco (1.9%), 28 Turkey (2.2%), 29 and Brazil (0%), 10 but a lower prevalence than that from Ghana (14.5%).…”
Section: Discussioncontrasting
confidence: 38%
“…Afşar et al reported that 1.38% of blood donors had HBsAg positivity 15 . Köse et al reported that 2.2% of the barbers and hairdressing employees in İzmir were positive for HBsAg and 0.4% of them were positive for Anti-HCV 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Anti-HCV seroprevalence was reported as 0.54% in a total of 1,076,495 units of blood 1 . In the study conducted in an İzmir hospital, the prevalence of Anti-HCV among blood donors was 0.42% 16 . Similarly, Yazan-Sertöz et al found a 0.3% rate of Anti-HCV positivity among 4537 blood donors in İzmir 14 .…”
mentioning
confidence: 99%
“…Previous studies have indicated that in developed countries, certain beauty treatments play an important role in the speared of HBV and HCV infection among barbers and their clients (8). Hepatitis B virus can survive on the instrument, tabletops and workbenches for at least seven days; therefore, it is important for the barbers to know their HBV status by being screened for the HBV surface antigen and antibody and to be vaccinated against HBV if found to be unprotected (4,9). Safe and protective vaccine against HBV is available throughout world including Iran.…”
Section: Introductionmentioning
confidence: 99%